2014
DOI: 10.1155/2014/392309
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ant Algorithms for Software Testing Cases Generation

Abstract: Existing ant colony optimization (ACO) for software testing cases generation is a very popular domain in software testing engineering. However, the traditional ACO has flaws, as early search pheromone is relatively scarce, search efficiency is low, search model is too simple, positive feedback mechanism is easy to porduce the phenomenon of stagnation and precocity. This paper introduces improved ACO for software testing cases generation: improved local pheromone update strategy for ant colony optimization, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…As per the study claim suggested approach outperforms the other algorithm mentioned above in terms of coverage capability and convergence speed. Yang, Man, and Xu [27]used modified ACO for software test case generation. This modified ACO introduces a new coefficient with the name Improved Pheromone Volatilization Coefficient for ACO (IPVACO) for pheromone update strategy.…”
Section: A Aco In Structural Testingmentioning
confidence: 99%
“…As per the study claim suggested approach outperforms the other algorithm mentioned above in terms of coverage capability and convergence speed. Yang, Man, and Xu [27]used modified ACO for software test case generation. This modified ACO introduces a new coefficient with the name Improved Pheromone Volatilization Coefficient for ACO (IPVACO) for pheromone update strategy.…”
Section: A Aco In Structural Testingmentioning
confidence: 99%
“…Yang et al [9] proposed a comprehensive improved ant colony optimization(ACIACO) whose performance was compared on the basis of efficiency and coverage with genetic algorithm and random algorithm. The results of the proposed approach signify that the ACIACO can improve the search efficiency, restrain precocity, promote case coverage, and reduce the number of iterations.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently the user session will be updated. For example if the initial user session retrieved from web log file is 0, 12,13,17,22,8,34,33,27,9 . Delete the node number 22,8,34 and assign 17 to pre and 33 to next.…”
Section: B11 Applying Abc In Regression Testing Of Web Application mentioning
confidence: 99%
“…al. in [3] presented a modified ACO approach for automated software testing. They presented new local pheromone update coefficient and compared the results with traditional random and genetic algorithm based techniques.…”
Section: Related Workmentioning
confidence: 99%